Economic Cooperation in Modern Economic History - Raftis, J. A. (Relations industrielles / Industrial Relations, 1952)
SummaryThe author, in this article wishes to show briefly the peculiar functioning of cooperative institutions in modern economic life. After a short historical review in order to show the many efforts made to organize the economy on the basis of common ownership of the instruments of production, he criticizes the principles set forth by the cooperative movement and then examines its actual structure. His attention is given to the problems arising from the application of cooperative principles in the modern economy. He concludes in suggesting that a practical educational programme making people aware of their industrial potential may perhaps be the only solution and will bring favourable results.